Wound healing by marigold (Calendula officinalis) and turmeric (Curcuma longa) paste: A comparative approach (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This experiment was conducted to evaluate the therapeutic potency of marigold flower (Calendula officinalis) and turmeric (Curcuma longa) rhizome paste in wound healing.Materials and methods: Thirty six aseptic surgical wounds were tooled in six non-pregnant black Bengal goats dividing them in 3 groups. Month long information and follow-up examinations along with complications such as edema, wound dehiscence, suture abscess, exudation etc. were studied. Wound healing was assessed by observing some morphological characters as well as histopathological changes of the wounded area.Results: Results revealed that negligible elevation of suture line (1.17±0.11 mm) and significant (P